Prespektif Kriminologi atas Kejahatan yang Dilakukan terhadap Anak - imran siswadi (UIN Sunan Kalijaga Yogyakarta, 2012)
The Indonesian people put a man on the overall status and dignity as creatures of God Almighty. It is recognized and acknowledged that the Indonesian people have basic needs that must be met, including children who have a need to grow and develop naturally. In order to realize the human resource Indonesia qualified coaching is continuously required for survival, growth and physical development, mental and social development as a whole as well as the protection of all the possibilities that would endanger them and the nation in the future. Crime is a social problem which is an integral part ofhuman life, because of social problems as a result of human culture. Social problem varies in each community due to the level of cultural development, environment, nature of the population in which people live. Crime always causeunrest in the community. Restlessness is a symptom of the lack of social welfare, peace and happiness. Today the growing crime in accordance with the times, especially with the development of technology and science, arise various forms of new crimes. With the rapid advancement of technology today, cause of information through mass media such as magazines, newspapers, televisionand so can provide information on crimes in various forms. Psychologically crimes committed against minors is not only the responsibility of the parents, judges, society and government but its scope is wider continuation of the country's future, because in their hands the future of our country. To preventcrimes committed against children, the role of law enforcement agencies is necessary in accordance with the duties and powers of each, which is continuously upgraded. The law enforcement should really as public protector not just as a protection for perpetrators.